Curricular environmentalization. The Covid-19, new emphases for education - Bravo, Maria Teresa (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Curricular environmentalization has been promoted from the field of environmental education for environmental training—with criteria to ensure the sustainability—of future generations that will carry out the professional practices for which they have been trained. Higher education institutions are considered agents of social change, providing solutions to critical social problems and training future professionals. However, they play a paradoxical role because, to a large extent, they have contributed to the emergence ofenvironmental problems and unsustainability. It has been proposed to critically assess the type of professional training that has been promoted by the universities, in order to corroborate their commitment to the care and maintain the ecosystem properties of nature. In this article, we provide a summary of the directions of curriculum environmentalization before the Covid-19 pandemic. Some views on the appearance of the coronavirus in the life of human beings are discussed. Because of that, the directions now being followed in the context of curriculum environmentalization feature new emphases on environmentalproblems for educational spaces.